Performance Tests of Cessna 172S Magnetos Under Various Thermal Conditions - Muhammad Nur Cahyo Hidayat Nasrullah; Sabam Danny Sulung; Untung Lestari Nur Wibowo; Ikhwanul Qiram (Journal of Science Technology (JoSTec), 2023)
Magneto serves as the ignition source in the combustion process of piston aircraft engines. Typically, spark-ignition aircraft like the Cessna 172SP are equipped with two ignition systems (dual magnetos). Dual magnetos are installed so that if one system fails, the aircraft can still continue its flight. During the engine startup process, the magneto plays a significant role as the ignition source for the initial combustion before the aircraft engine comes to life. In the case experienced by pilots at the Indonesian Civil Pilot Academy Banyuwangi, starting the engine became challenging when the aircraft had been previously used for a flight. Therefore, this research is conducted to address the underlying causes of this issue. The parameters examined in this research include outside air temperature (OAT), Cylinder Head Temperature (CHT), and Exhaust Gas Temperature (EGT). Data were collected regarding the duration of the engine startup process. The duration time for starting the engine was found to be the highest at an exhaust gas temperature of 135 °F, a cylinder head temperature of 180 °F, and an outside air temperature of 35 °F, with a duration time of 6.8 seconds. Conversely, the shortest engine startup duration was observed at an exhaust gas temperature of 75 °F, a cylinder head temperature of 75 °F, and an outside air temperature of 26 °F, resulting in a duration time of 1.6 seconds.